Cochlear Implantation in Hearing-Impaired Elderly: Clinical Challenges and Opportunities to Optimize Outcome - Illg, Angelika; Lenarz, Thomas (Frontiers in Neuroscience, 2022)
Cochlear Implant (CI) overall provides very good outcome, but speech comprehension outcome in the elderly is more variable. Several clinical factors play an important role. The management of residual hearing, the presence of comorbidities, and especially the progression of cognitive decline seem to be the clinical parameters that strongly determine the outcome of cochlear implantation and need to be discussed prospectively in the consultation process with the elderly hearing impaired. In the context of this review article, strategies for dealing with these will be discussed. Timely cochlear implantation should already be considered by hearing aid acousticians or practicing otolaryngologists and communicated or initiated with the patient. This requires intensive cooperation between hearing aid acousticians and experts in the clinic. In addition, residual hearing and comorbidities in elderly need to be considered in order to make realistic predictions about speech comprehension with CI. Long-term aftercare and its different implementations should be discussed preoperatively, so that the elderly hearing-impaired person feels well taken care of together with his or her relatives. Hearing-impaired elderly patients benefit most from a CI in terms of speech comprehension if there is a large cochlear coverage (electrical or acoustic-electrical) and the therapy is not hampered by comorbidities, especially cognitive decline.